ANCAMAN KENAIKAN MUKA AIR LAUT BAGI NEGARA-NEGARA DI KEPULAUAN PASIFIK - Bayu Wahyudin (Review of International Relations, 2020)
The increase in the average temperature of the earth is experiencing global warming. Of the many impacts, sea level rise is one of the most important impacts because it can eliminate the existence of certain state entities. An island state with distinctive features and issued consisting of small islands is the party most threatened. This threat is slow but surely continues to haunt residents living in these island-states, for example the Pacific islands. The impact of this challenge is not only on the environment, but also on the social life of residents living in this area. If one day the area they now live in is completely submerged, then they must find a new place to live (climate change refugees). Therefore, the Pacific islands, specifically those who are members of the Melanesian Spearhead Group (MSG) and the Pacific Islands Forum (PIF), make various efforts in overcoming this problem. This paper uses the help of the green political paradigm (Green Politic) as a reference in seeing the phenomena associated with MSG and PIF in the Pacific countries.